The Role of Government Agencies on Tourism related SMEs in Lenggong Valley, Perak - Mhd Rashid, Munira; Jaafar, Mastura; Dahalan, Norziani (AENSI, 2015)
As a new UNESCO World Heritage Site, strong supervision by the government is essential for Lenggong Valley to excellently develop in tourism and economic sector. A study was conducted on the tourism related SMEs (micro, small and medium enterprise) in order to measure the government agencies supports provided to the businesses. The study discovered that many government agencies have been supporting the tourism related SMEs and several different types of assistance are provided include capital, loan, course and training, marketing, consultancy, allocation and equipment support. The government agencies assistance is crucial to ensure the tourism related SMEs maximise the advantages from potential tourism development.